THE RESILIENCE OF PEOPLE LIVING WITH HIV AIDS; BETWEEN SEX AND MARITAL STATUS - Dewi Purnamawati; Nurfadhilah; Rohimi Zamzam; Karina Amalia (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2022)
People living with HIV and AIDS (PLWHA) are a vulnerable population with psychosocial problems, including changes in status in society and stigma. PLWHA is prone to mental health disorders, including stress and depression, therefore a positive coping mechanism with resilience is needed. This study aims to identify the relationship between sex and marital status with resilience in PLWHA. This research was conducted in Bogor City using a cross-sectional design. The population is PLWHA in Bogor City. Samples were taken randomly from 98 PLWHA. Data were collected using an online questionnaire and analyzed bivariately with the Chi-square test. The results showed that 48% of PLWHA had negative resilience. Negative resilience is shown on the points of ability to cope with stress (36%), belief in finding love (39%), and belief in having children (38%). Meanwhile, high positive resilience is shown in the ability to respect others (79.5%) and believe in their own religion (74.4%). There is a significant relationship between gender (p-value, 0.005; OR=5.5) and marital status (p-value, 0.018; OR=2.9) with resilience in PLWHA. PLWHA who are female and married has a positive chance of resilience compared to male and unmarried sex. Psychosocial assistance activities are needed to increase resilience in PLWHA, especially for PLWHA who are not married and female.